Detection of Toxoplasma gondii in aqueous humour by the polymerase chain reaction. - Aouizerate, F (1993)
Ocular toxoplasmosis is the most frequent infectious cause of chorioretinal inflammation in immunocompetent patients. Nowadays, the biological diagnosis of ocular toxoplasmosis requires serological tests and anterior chamber puncture to detect the local production of specific antibodies. A new technique is described to detect Toxoplasma in aqueous humour by a polymerase chain reaction in which the target is a specific ribosomal DNA segment. Sixty eight patients (71 eyes) were included; 59 (83%) eyes were suspected of having ocular toxoplasmosis. Of these 59 eyes, 15 (25.4%) had characteristic fundus lesions with obvious intraocular inflammation signs and 44 (75%) had retinal scar of ocular toxoplasmosis without clinically detectable inflammation. Twelve (17%) eyes had uveitis of non-Toxoplasma origin and constituted the control group. The parasite was present in aqueous humour in 20 (33.8%) cases. No false positives were detected. The sensitivity of the test is reduced by the low numbers of the sample. The combination of this technique with Witmer-Desmonts coefficient increases the probability of making a biological diagnosis of ocular toxoplasmosis. The physiopathological value of this technique is emphasised and the presence of tachyzoites in the anterior chamber is suggested. This should be a very promising technique for the diagnosis of ocular toxoplasmosis.